Ibn Khaldūn’s ʻAṣabiyyah Theory as an Analytical Framework in Contemporary Global Historical Historiography - Eun Kyeong Yun; Daniel Ross; Leonid Issaev (Yayasan Albahriah Jamiah Indonesia, 2026)
Global historiography continues to evolve toward a more integrated reading of world history, although some interpretive frameworks remain dominated by Western historiographic perspectives, and the relationship among social cohesion, the formation of power, and the transformation of civilizations across regions has yet to receive an adequate conceptual explanation. Studies on the theory of ʻAṣabiyyah generally focus on Islamic history or regional political dynamics, while its use as an analytical tool in global historiography is still limited. This study aims to reconstruct Ibn Khaldūn’s ʻAṣabiyyah theory as an analytical framework for explaining the relationship among collective solidarity, political legitimacy, power expansion, and civilizational change in global historiography. This study uses a qualitative approach based on literature studies through historiographical analysis, conceptual analysis, and critical interpretation of the Muqaddimah as a primary source and recent academic literature as a secondary source. The analysis yields a conceptual reconstruction that positions ʻAṣabiyyah as a historical mechanism linking social cohesion, the consolidation of political authority, the capacity for collective mobilization, the expansion of power, the process of institutionalization, the decline of solidarity, and the cycle of civilizational transformation across regions and historical contexts. This reconstruction demonstrates the ability of Ibn Khaldūn’s theory to explain historical dynamics through the integrated interaction of social and political factors, and expands the function of ʻAṣabiyyah from a historical concept to an interpretive instrument in global historiography. The findings of this study enrich the conceptual framework of global historiography by integrating the Islamic intellectual tradition as a systematic and relevant analytical perspective, broadening the horizons of world historical explanation.